LC-MS/MS assisted biomonitoring of ropivacaine and 3-OH-ropivacaine after plane block anesthesia for cardiac device implantation - Butiulca, Mihaela; Farczadi, Lenard; Vari, Camil Eugen; Imre, Silvia; Pui, Mihai; Lazar, Alexandra (Frontiers in Molecular Biosciences, 2023)
Ropivacaine is a popular local anesthetic used for regional anesthesia or for pain management. Although designed as an enantiomerically pure drug, an aspect that reduces the adverse effects, its toxicological effects are still a risk. As such, biomonitoring to assure appropriate dosage and bioavailability are essential to avoid complications during or post-surgery. The study focused on developing a sensitive, selective, and accurate liquid chromatography -mass spectrometry (LC-MS/MS) method which facilitates the biomonitoring of ropivacaine and its main metabolite in plasma after regional anesthesia using ropivacaine. The method was validated with regards to all relevant parameters, such as sensitivity, selectivity, accuracy, precision, and the effect of sample matrix. The method was successfully used in a pilot study, which included one patient undergoing plane block anesthesia for cardiac device implantation. The results showed the method is appropriate for its intended purpose and could even be used in other, similar applications.